Four cases of cystitis induced by the anti-allergic drug tranilast - Nishida, T (Hinyokika kiyo. Acta urologica Japonica, 1985)
First, the cases of two patients with intractable cystitis are presented. The first case was a 72-year old man who was admitted to our clinic with bladder symptoms (pollakisuria, pain on urination, hematuria and so forth) for about one month. These symptoms were not relieved by several kinds of antibiotic therapy. For the previous three months he had been suffering from asthma bronchiale. Rizaben (tranilast) was administered for more than two months. An excretory urogram showed normal renal function, but a small bladder with trabeculation. Voiding cystourethrograms revealed bilateral VUR. Cystoscopy disclosed remarkable red areas in the bladder mucosa. A bladder biopsy was done and the pathological finding was cystitis chronica. Intravesical installation of AgNO3, steroid administration, anti-histamic and anti-allergic therapy did not resolve these symptoms. However, Chinese medicines (Chorêto and Ryutanshakantõ) were effective. The second case was a 39-year old woman who visited our clinic complaining of bladder symptoms with hematuria for more than two months. In the past, she had suffered from asthma bronchiale. Rizaben (tranilast) was administered for three months. On cystoscopic examination, a small amount of intravesical coagula and erythematous, edematous areas with petechiae, were observed. The intravesical installation of AgNO3, anti-histamic and antiallergic therapy and gamma-globulin were not effective, but Chinese medicine was effective. Two other cases of cystitis due to Rizaben are presented briefly. Including our cases, 24 cases of cystitis chronica or eosimophilic cystitis due to Rizaben have been reported recently